Some Important Concepts of Teaching Evolution in the Indonesian High School - Muhammad Ja’far Luthfi; Sindi Farhana (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2018)
The theory of evolution explains that diversity of many life forms can exist as the result of genetic changes. The idea of evolution can be accepted by most scientist, however it is also rejected by other community because its contradiction with some religious values. The most controversial issue is that the theory of evolution tries to explain abouth the origin of human. It is difficult to deal with that controversy because it involves science, philosophy, and theology, in which each group view the theory from its own specialization without considering other aspects. Some moslem scientist try to accept or reject the theory of evolution by using al Qur’ran as their reason. Basically there is no controversy between al Qur’an and science although al Qur’an does not give detail explanation for all science or theories. The purpose of that explanation is to show the mighty of Allah SWT and encourage Moslem ummah to arrange more observation and research.